Less Than Half of Patients Recover Within 2 Weeks of Injury After a Sports-Related Mild Traumatic Brain Injury: A 2-Year Prospective Study. Issue 2 (March 2020) - Kara, Stephen; Crosswell, Hannah; Forch, Katherine; Cavadino, Alana; McGeown, Josh; Fulcher, Mark
Abstract : Objective: To describe clinical recovery time and factors that might impact on recovery after a sports-related mild traumatic brain injury (SR-mTBI; concussion). Design: Prospective cohort study (level IV evidence). Setting: New Zealand Sports Concussion Clinic. Participants: Eight hundred twenty-two patients presenting within 14 days of a SR-mTBI/concussion over a 2-year period. Main Outcome Measures: Clinical recovery measured as number of days after injury. Interventions Methods: Participants were assessed and managed using a standardized protocol consisting of relative rest followed by controlled cognitive and physical loading. A reassessment was performed 14 days after injury with initiation of an active rehabilitation program consisting of a subsymptom threshold exercise program ± cervicovestibular rehabilitation (if required) for participants who remained symptomatic. Participants were then assessed every 2 weeks until clinical recovery. Results: A total of 594 participants were eligible for analysis (mean age 20.2 ± 8.7 years, 77% males) and were grouped into 3 age cohorts: children (⩽12 years), adolescents (13-18 years), and adults (≥19 years). Forty-five percent of participants showed clinical recovery within 14 days of injury, 77% by 4 weeks after injury, and 96% by 8 weeks after injury. There was no significant difference in recovery time between age groups. Prolonged recovery was more common in females ( P = 0.001), participants with "concussion modifiers" ( P = 0.001), and with increased time between injury and the initial appointment ( P = 0.003). Conclusions: This study challenges current perceptions that most people with a SR-mTBI (concussion) recover within 10 to 14 days and that age is a determinant of recovery rate. Active rehabilitation results in high recovery rates after SR-mTBI. Abstract : Supplemental Digital Content is Available in the Text.